COMBINATION OF MARMET MASSAGE THERAPY AND STIMULATION OF ENDORPIN, OXYTOCIN, AND SUGGESTIVE MASSAGE (SPEOS) ON INCREASED BREAST MILK PRODUCTION - Rosa, Eni; Rita Kamalia; Nelly Rustiati; Umar Hasan Martadinata; Vina Ameliantika Putri (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Insufficient milk production is often a problem for breastfeeding mothers, which can affect the health and development of the baby. The combination of Marmet's massage therapy and Stimulation of Endorphins, Oxytocin, and Suggestive Massage (SPEOS) has been proposed as an effective method to increase milk production. This study aims to evaluate the effectiveness of the combination of Marmet massage therapy and SPEOS on increasing breast milk production in breastfeeding mothers.This study uses a case study design with a nursing process approach. Two breastfeeding mothers with the problem of inadequate milk supply were the subjects of the study. The intervention involved breastfeeding education and the application of Marmet massage and SPEOS for 4 days. Data were collected through interviews, observations, and a checklist sheet to record the frequency of breastfeeding and frequency of infant urination. The results showed that in the first client, the frequency of breastfeeding increased from 6 times before the intervention to 10 times after the intervention. In addition, the frequency of infant urination also increased from 5 times before the intervention to 8 times after the intervention. Similar results were also seen in the second client, where the frequency of breastfeeding increased from 3 times before the intervention to 10 times after the intervention, while the frequency of baby's BAK increased from 4 times before the intervention to 9 times after the intervention. These improvements indicate that the combination of Marmet and SPEOS massage is effective in increasing breastmilk production, breastfeeding frequency, and infant voiding frequency, which are indicators of adequate breastmilk intake and good hydration for infants. The combination of Marmet's massage therapy and SPEOS is effective in increasing breast milk production, breastfeeding frequency, and infant voiding frequency. This intervention can be a holistic non-pharmacological alternative to support successful breastfeeding and improve the quality of life of mothers and infants.